Smart collection routing problems: an optimization approach - Tan, Nicklaus Jun Wei (Nanyang Technological University, 2022)
Given the recent years of ever-growing emphasis on the search for the next efficient, environmentally friendly, and cost-effective waste collection management system. Along with it came the emergence of the Internet of Things (IoT) which allowed the trash bin’s fill-level to be captured and transmitted to the cloud. Hence, a three-phase heuristic data routing model was developed to bring improvements over the traditional blind collection. The final evaluation indicates that: 1) the suitable approaches for different bin fill-level increment scenarios; 2) the improvements in terms of total route distance and total vehicles required; 3) the trade-offs are given a certain approach.